2021
DOI: 10.1007/s12020-021-02659-4
|View full text |Cite
|
Sign up to set email alerts
|

Early post-natal life stress induces permanent adrenocorticotropin-dependent hypercortisolism in male mice

Abstract: Purpose It has been hypothesized that specific early-life stress (ES) procedures on CD-1 male mice produce diabetes-like alterations due to the failure of negative feedback of glucocorticoid hormone in the pituitary. The aim of this study is to investigate the possible mechanism that leads to this pathological model, framing it in a more specific clinical condition. Methods Metabolic and HPA-related hormones of stressed mice (SM) have been analyzed immediately after stress procedures (21 postnatal day, PND) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…On the other hand, other data support the idea that aberrant expression of one or more GPCRs and their ligands in adrenal tissues is a secondary rather than a primary event (71). Interestingly, very recent evidence from animal studies suggests that chronic stress in early life can induce persistent up-regulation of the HPA axis that generates endocrine, metabolic, and somatic alterations similar to those found in ACTH-dependent human ACTHdependent hypercortisolism (72).…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, other data support the idea that aberrant expression of one or more GPCRs and their ligands in adrenal tissues is a secondary rather than a primary event (71). Interestingly, very recent evidence from animal studies suggests that chronic stress in early life can induce persistent up-regulation of the HPA axis that generates endocrine, metabolic, and somatic alterations similar to those found in ACTH-dependent human ACTHdependent hypercortisolism (72).…”
Section: Discussionmentioning
confidence: 89%
“…However, research has been shown that exposure to glucocorticoids in utero is associated with increased adrenocortical function in juvenile period with increased fasting cortisol concentrations in adults [139,140]. The upregulation of postnatal HPA function in other species may reflect changes in the HPA axis at the level of the hypothalamus, pituitary or adrenal gland itself [141,142]. Previous studies that have shown maternal and fetal/newborn cortisol levels are correlated and maternal cortisol levels are associated with reactivity of the newborn HPA axis [22,143].…”
Section: Discussionmentioning
confidence: 99%
“…After being stressed in early life, the mice developed an autonomous pituitary ACTH secretion with GC excess persisting even after the resolution of the stressful period. This was confirmed by high ACTH and corticosterone levels and, clinically, by a significant increase in body weight and fasting plasma glucose levels [ 33 ].…”
Section: Pathophysiology Of Pituitary and Adrenal Mild Hypercortisolismmentioning
confidence: 98%